(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2020)
The new paradigm of education requires that a teacher in general and specifically PAK teachers must improve classroom governance properly and creatively. Therefore, a class management with an innovative atmosphere is needed. This effort was made to improve the quality of learning in the classroom and encourage students to learn. For this reason, classroom management relating to classroom management is important to support an effective teaching and learning environment in the classroom. Therefore, a teacher must avoid the conventional habits or old ways, do not always pay attention to classroom management, this is very influential on the teacher’s teaching style and learning styles of students. Key words: Classroom management, PAK learning, innovative teaching and learning.